Jakiej syntezy literatury najnowszej potrzebuje slawistyka? - Thaidigsmann, Karoline (Postscriptum Polonistyczne, 2025)
Based on the observation that there is a lack of syntheses of contemporary Polish literature that are accessible in terms of content and language for students and other interested readers abroad, I undertake reflections on what kind of synthesis of contemporary literature Slavic studies, more precisely: Polish studies abroad needs. I approach this issue from the perspective of a researcher and lecturer in Polish literature at a German university. The attempts to answer the questions posed are closely related to two projects in which I am involved. One of them is a Polish-German project concerning the contemporary history of Polish literature for German-speaking readers. The second concerns research on the function of children’s literature in diverse cultural contexts. I treat both in this article as an attempt to cross boundaries and open new perspectives for the creation of literary syntheses. I demonstrate that the first project aligns with constellational thinking and the belief that, today, the task of literary history can be understood above all as proposals for how to think about the development of literature, and thus, how to assist in shaping mature recipients of (the history of) literature. I also point out that writing a synthesis of contemporary Polish literature for the German reader requires many pragmatic decisions which influence the form and thematic scope of the presented content. The Polish-German project on literary history eliminates the distinction between popular and high literature, as well as between fiction and nonfiction. It also, at least to some extent, removes the division between children and adult audiences. Referring to four aspects of “children’s” literature (multimodality, crossover, cultural code, experimental aesthetics), I argue why the latter is necessary.
Online veröffentlicht: 20. August 2025
Gesehen am 21.01.2026